Strategi Peningkatan Penjualan Makanan Tradisional Sunda Melalui Daya Tarik Produk Wisata Kuliner di The Jayakarta Bandung Suite Hotel & Spa - Fajri, Ilham (Universitas Pendidikan Indonesia, 2018)
The increase in the number of visitors to the hotel each year has the potential to further develop, but the problem is the appeal of Traditional Sundanese Foods found in the hotel is not known by many people. This study aims to formulate the appropriate sales promotion strategy to be applied at The Jayakarta Bandung Suite Hotel Spa through SWOT analysis approach. Where based on SWOT analysis results, external factors with the highest score that affect the increase in sales is an opportunity factor is branding the city of Bandung as a culinary destination, while the highest threat is food from other countries.Â Internal factor with highest score is the strength factor that is the appeal of the menu offered, while the weakness factor is promotion. A suitable strategy to be applied for market is penetration strategy and product improvement strategy.